Pengaruh Social Media Marketing dan Kualitas Produk Terhadap Loyalitas Konsumen pada Thrift Shop Gartenhart di Malang - M. Ilmi Santriawan Putra; Ayu Sulasari (Indo Publishing, 2026)
The growth of thrift shop businesses among young generations has been increasing rapidly, particularly in the Malang Raya area. Thrift Shop Gartenhart is one of the businesses that takes advantage of this trend by utilizing Instagram as its main marketing platform. However, consumer loyalty remains fluctuating due to inconsistencies in product quality and digital interaction. This study aims to analyze the influence of social media marketing and product quality on consumer loyalty at Thrift Shop Gartenhart in Malang. The population of this study consisted of all Instagram followers of Gartenhart, totaling 4,012 accounts. The sample was determined using purposive sampling with the criteria of consumers who had made at least two purchases. Based on this criterion, 98 respondents were selected as the research sample. This study employed a quantitative descriptive approach with a questionnaire as the research instrument, and the data were analyzed using multiple linear regression with the assistance of SPSS. The results showed that social media marketing had a positive and significant effect on consumer loyalty, with a t-value of 3.240 > t-table 1.978. Product quality also had a positive and significant effect, with a t-value of 5.291 > t-table. Simultaneously, both variables significantly influenced consumer loyalty, with an F-value of 47.063 > F-table 3.07 and a significance level of 0.000. The coefficient of determination (R²) was 0.425, indicating that 42.5% of consumer loyalty was influenced by social media marketing and product quality, while the remaining percentage was influenced by other factors outside this study.In conclusion, social media marketing and product quality have a positive and significant effect on consumer loyalty. Therefore, Thrift Shop Gartenhart needs to maintain consistency in its social media content strategy and improve product selection and quality control standards to strengthen consumer loyalty amid the increasingly competitive preloved fashion business.